The promotion of electronic filing technology - Ahmad, Jasmine; Abdul Aziz, Rozainun; Abdul Rahim, Memiyanty; Che Hamid, Khamsi; Md Nen, Zurina (2011)
The emergence of digital service has put governments under an increasing pressure to improve the delivery of public services in cost-effective ways. Electronic tax filing system (after this referred as e-Filing) is one of the e-government applications that has the potential in ensuring the tax collection process efficiently. However, there are many excuses given by the taxpayers for not using the e-filing service provided by the government. This research intends to narrow the gap between the expectation of current e-Filing service in Malaysia and human behaviour that is motivation in accepting the technology. Till date, not many studies or literatures incorporate motivational elements in technology acceptance model that are fundamental to the taxpayer's decision whether to use e-Filing or not. The electronic filing technology and motivation acceptance model (e-FTMAM) was inspired from Siegel (2008) modified and used in this research to offer recommendations in minimizing resistance and persuading the taxpayers' acceptance in using e-Filing from Malaysia scenario. The results can assist e-government service design not only to increase service quality but also enlarge the acceptance for the taxpayers towards e-filing. e-FTMAM will enable taxpayers to shift their decision from unwilling to use to more trust and willing to accept and adopt on the e-government service. Thus, this would assist Inland Revenue Board in offering a more favourable climate for exercising voluntary compliance by taxpayers in promoting and educating public. Ultimately, to establish an environment in which citizens are induced to comply with tax laws voluntarily. This will lead to the registration of more taxpayers using e-filing, effective recovery action and hence greater tax revenue to the country. This is also about making it easy- as simple as possible for taxpayer to comply. This research investigates why some Malaysian taxpayers resisted in using e-Filing. The extended model called electronic filing technology and motivation model (eFTMAM) was modified and inspired by two previous model. These models are the technology acceptance model (TAM) developed by Davis (1985) and the commitment and necessary effort (CANE) model of motivation developed by Clark (1998).